PROBLEMS AND SOLUTIONS INVOLVED IN DIRECT SYNTHESIS OF ALLYLCHLOROSILANES - YEON, SH; LEE, BW; KIM, SI; JUNG, IN (AMER CHEMICAL SOC, 1993)
Direct synthesis of allylchlorosilanes has been reinvestigated by reacting elemental silicon simultaneously with allyl chloride and hydrogen chloride in the presence of copper catalyst using a stirred reactor equipped with a spiral band agitator at a carefully controlled temperature between 220 and 320-degrees-C. Allyldichlorosilane was obtained as the major product and allyltrichlorosilane as a minor product along with trichlorosilane and tetrachlorosilane derived from the reaction between elemental silicon and hydrogen chloride, but diallyldichlorosilane was obtained only in a trace amount. The decomposition of allyl chloride was suppressed and the production of diallyldichlorosilane reduced by adding hydrogen chloride to the allyl chloride reactant. The polymerization problem in the distillation process of the products due to diallyldichlorosilane was eliminated. Cadmium was a good promoter for the reaction, while zinc was found to be an inhibitor.
Keywords: ORGANO-SILICON COMPOUNDS